Focused and Sustained Attention Is Modified by a Goal-Based Rehabilitation in Parkinsonian Patients - Ferrazzoli, Davide; Ortelli, Paola; Maestri, Roberto; Bera, Rossana; Gargantini, Roberto; Palamara, Grazia; Zarucchi, Marianna; Giladi, Nir; Frazzitta, Giuseppe (Frontiers in Behavioral Neuroscience, 2017)
Rehabilitation for patients with PD is based on cognitive strategies that exploit attention. Parkinsonians exhibit impairments in divided attention and interference control. Nevertheless, the effectiveness of specific rehabilitation treatments based on attention suggests that other attentional functions are preserved. Data about attention are conflicting in PD, and it is not clear whether rehabilitative treatments that entail attentional strategies affect attention itself. Reaction times (RTs) represent an instrument to explore attention and investigate whether changes in attentional performances parallel rehabilitation induced-gains. RTs of 103 parkinsonian patients in “on” state, without cognitive deficits, were compared with those of a population of 34 healthy controls. We studied those attentional networks that subtend the use of cognitive strategies in motor rehabilitation: alertness and focused and sustained attention, which is a component of the executive system. We used visual and auditory RTs to evaluate alertness and multiple choices RTs to explore focused and sustained attention. Parkinsonian patients underwent these tasks before and after a 4-week multidisciplinary, intensive and goal-based rehabilitation treatment (MIRT). UPDRS III and TUG were assessed at the enrolment and at the end of MIRT to evaluate the motor-functional effectiveness of treatment. We did not find differences in RTs between parkinsonian patients and controls. Further, we found that improvements in motor-functional outcome measures after MIRT (p<0.0001) paralleled a reduction in multiple choices RTs (p=0.014). No changes were found for visual and auditory RTs. Correlation analysis revealed no association between changes in multiple choices RTs and improvements in UPDRS-III and TUG. These findings indicate that alertness, as well as focused and sustained attention, are preserved in “on” state. This explains why Parkinsonians benefit from a goal-based rehabilitation that entails the use of attention. The reduction in multiple choices RTs suggests a positive effect of MIRT on the executive component of attention and indicates that this type of rehabilitation provides benefits by exploiting executive functions. This ensues from different training approaches aimed at bypassing the dysfunctional basal ganglia circuit, allowing the voluntary execution of the defective movements. These data suggest that the effectiveness of a motor rehabilitation tailored for PD lies on cognitive engagement.